Features of epizootic process of monieziasis and mixed helminthiasis in sheep of the Republic of Tajikistan - I. Sh. Shodmonov (Российский паразитологический журнал)
Objective of research: The study of features of epizootic process of monieziasis and mixed helminthiasis in sheep of Tajikistan. Materials and methods: Research was conducted in different sheep farms including «Charvozor» of Vakhsh region, «Danghara» of Danghara region, «Chorubkul» of Temurmaliksk region and other private farms in 2015-2017. Fecal samples from 548 lambs, 636 from young and 717 from adult sheep were investigated in different months using Fuelleborni method of flotation, and Berman technique for the diagnosis of dictyocaulosis. The research results were statistically processed. Results and discussion: Significant differences in seasonal dynamics of monieziasis in sheep caused by Moniezia expansa and М. Benedeni as well as dependence of the infestation of different Moniezia species on the age of animals was determined. In monieziasis occurring in spring and summer seasons (causative agent M. expansa) lambs become infected in May, the peak of infection falls on July. Towards autumn, a decrease in infection was observed, and in winter M. expansa rarely found. Adult sheep were mostly infected with M. benedeni, and in lambs this infection was found in July-August; the maximum level of infection was observed in March of the following year. M. benedeni remained viable in lambs within 10-12 months in regular superinfections (September-October) during the whole winter season. At the beginning of spring, spontaneous discharge of moniezia from sheep body occured. Monieziasis (M. expansa) in a severe form + dictyocaulosis as well as monieziasis+ hemonhosis+nematodirosis+ strongyloidosis at different combinations of components of parasitic cenosis occur in lambs of 2,5 to 6 months of age. Two and three-component infections are most common in sheep from joint-stock and individual sheep farms of piedmont and mountain region of Tajikistan.